2002
DOI: 10.1038/sj.leu.2402477
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Differentiation (MyD)/Growth Arrest DNA Damage (GADD) genes in tumor suppression, immunity and inflammation

Abstract: Myeloid differentiation (MyD) primary response and growth arrest DNA damage (Gadd) genes comprise a set of overlapping genes, including known (IRF-1, EGR-1, Jun) and novel (MyD88, Gadd45␣, MyD118/Gadd45␤, GADD45␥, MyD116/ Gadd34) genes, that have been cloned by virtue of being coordinately induced upon the onset of terminal myeloid differentiation and following exposure of cells to stress stimuli. In recent years it has become evident that MyD/Gadd play a role in blood cell development, where they function as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 202 publications
(214 reference statements)
2
50
0
Order By: Relevance
“…As the Per2 gene is regulated by Clock, it is possible that the expression of this protein might be involved in DNA damage-induced apoptosis. The analysis of the expression profile showed that several DNA damage-inducible genes such as members of the growth-arrest and DNA damage (GADD) family that block cell-cycle progression (Liebermann and Hoffman, 2002) and cyclin genes were controlled by circadian regulators (Fu et al, 2002). Taken together, these results indicate that the cell cycle-regulating mechanism in cisplatin-resistant cells is regulated by Clock.…”
Section: Discussionmentioning
confidence: 91%
“…As the Per2 gene is regulated by Clock, it is possible that the expression of this protein might be involved in DNA damage-induced apoptosis. The analysis of the expression profile showed that several DNA damage-inducible genes such as members of the growth-arrest and DNA damage (GADD) family that block cell-cycle progression (Liebermann and Hoffman, 2002) and cyclin genes were controlled by circadian regulators (Fu et al, 2002). Taken together, these results indicate that the cell cycle-regulating mechanism in cisplatin-resistant cells is regulated by Clock.…”
Section: Discussionmentioning
confidence: 91%
“…We also suggest that mitochondrial ROS and CHOP-10/GADD153 belong to the intracellular O 2 sensing mechanism of adipose cells. This signaling pathway could be involved in limiting growth of adipose tissue as described in other tissues (32,33). Moreover, ROS generation linked to mitochondrial dysfunction could be directly involved in adipose tissues alterations associated with metabolic disorders (34).…”
Section: Discussionmentioning
confidence: 99%
“…The GADD45 proteins share 55 to 58% sequence identity. The three GADD45 genes are all inducible by cellular stresses, although optimal stimuli for each gene appear to be different (25). The expression profiles of the three GADD45 genes are also distinct in various tissues (34).…”
mentioning
confidence: 99%
“…The GADD45 gene was originally identified as a UV-inducible gene in Chinese hamster cells (14). The human genome encodes three GADD45-like proteins, GADD45␣ (the original GADD45), GADD45␤ (MyD118), and GADD45␥ (CR6 or OIG37) (25,44). These will be referred to collectively as the GADD45 proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation